Cross-Cultural Validation of Mood Profile Clusters in a Sport and Exercise Context - Quartiroli, Alessandro; Parsons-Smith, Renée L.; Fogarty, Gerard J.; Kuan, Garry; Terry, Peter C. (Frontiers in Psychology, 2018)
Mood profiling has a long history in the field of sport and exercise. Several novel mood profile clusters were identified and described in the literature recently (Parsons-Smith, Terry, & Machin, 2017). In the present study, we investigated whether the same clusters were evident in an Italian language, sport and exercise context. The Italian Mood Scale (ITAMS; Quartiroli, Terry, & Fogarty, 2017) was administered to 950 Italian-speaking sport participants (659 females, 284 males, 7 unspecified; age range = 16–63 yr., M = 25.03, SD = 7.62) and seeded k-means clustering methodology applied to the responses. Six distinct mood profiles were identified, termed the iceberg, inverse iceberg, inverse Everest, shark fin, surface, and submerged profiles, which closely resembled those reported among English-speaking participants (Parsons-Smith et al., 2017). Significant differences were found in the distribution of specific mood profiles across gender and age groups. Findings supported the cross-cultural generalizability of the six mood profiles and offer new research avenues into their antecedents, correlates and behavioral consequences in Italian-language contexts.